Static Standing Trunk Sway Assessment in Amputees – Effects of Sub-Threshold Stimulation - L. Ming-Yih; S. Kok-Soon; L. Chih-Feng (Applied Bionics and Biomechanics)
Sub-threshold electrical stimulation can enhance the sensitivity of the human somatosensory system to improve the balance control capability of elderly was shown in recent rehabilitation articles. The purpose of this study was to evaluate the postural sway of trans-tibial amputees when performing single leg quiet standing on firm surface. Four unilateral trans-tibial amputees who consecutively wore prosthetics over 2 years were recruited in this study. Subjects performed single leg quiet standing trails with sub-threshold electrical stimulation applied at the quadriceps muscle during the trails. Spatial co-ordinates for the determination kinematic data (sway distance) of the center of mass (COM) on second sacral (S2) were collected using an ultrasound-based Zebris CMS-HS system. The single leg quiet standing test is measure considered to assess postural steadiness in a static position by a spatial measurement. The common notion is that a better postural steadiness, i.e. less postural sway, allows for longer time single leg quiet standing. However, there is lack of evidence how postural steadiness during single leg quiet standing changes over time. In this article, we hypothesized that the static balance of single leg quiet standing could be improved for providing proprioceptive neuromuscular facilitation using sub-sensory stimulation in amputees. To test this hypothesis, a computerized sub-threshold low-level electrical stimulation device was developed and proposed for clinical study. Experimental results show that reduction in all of the postural sway indices (constant time sway length, max sway distance and average sway distance) and increase in single leg support time index during single leg quiet standing by applying sub-sensory stimulation. The single leg quiet standing test findings suggest that sub-threshold electrical stimulation rehabilitation strategies may be effective in improving static balance performance for amputees.